Efektivitas Sistem Informasi Akuntansi, Budaya Organisasi dan Kinerja Karyawan di Lembaga Perkreditan Desa Kecamatan Tegalalang - Dwipayana, I Gusti Ngurah Krisna; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2021)
Employee performance is a level of overall success for a person in carrying out a task. Good employee performance is driven by the effectiveness of the accounting information system and organizational culture. The purpose of this study was to provide empirical evidence in the effect of the effectiveness of accounting information systems and organizational culture on employee performance. This research conducted at the Village Credit Institutions in Tegalalang District. The number of respondent taken was 121 employees, with a purposive sampling method. Data collection was carried out using a questionnaire. The analysis technique used is multiple linear regression. The results showed that the effectiveness of the accounting information system and organizational culture had a positive effect on employee performance. Keywords: Effectiveness of Accounting Information Systems; Organizational Culture; Employee Performance.